The effects of subchronic exposure to NeemAzal T/S on zebrafish (Danio rerio). Issue 3 (16th March 2018) - Plhalova, Lucie; Blahova, Jana; Divisova, Lenka; Enevova, Vladimira; Casuscelli di Tocco, Francesca; Faggio, Caterina; Tichy, Frantisek; Vecerek, Vladimir; Svobodova, Zdenka
ABSTRACT: The objective of the study was to investigate the subchronic effects of the insecticidal preparation NeemAzal T/S at concentrations of 3, 10 and 30 mg/L on the mortality, growth and histopathology of juvenile zebrafish ( Danio rerio ), as well as its related effects on selected indices of oxidative stress during a 28-day toxicity test. The juvenile growth toxicity test was performed according to OECD Guidelines 215 (Fish, Juvenile Growth Test). The results of this study indicate that these tested concentrations of NeemAzal T/S (containing 1% of the active ingredient azadirachtin A) affect fish growth and have a negative influence on the indices of oxidative stress in the juvenile stage of zebrafish, as well as cause mild histopathological changes in liver tissue.